Conducta obstétrica en primigesta adolescente con feto malformado por defecto de la pared abdominal - Moreta Obando, Shirley Silvana (2023)
Congenital malformations of the abdominal wall are considered to be increasing with respect to the incidence rate of this pathology, occurring due to multiple possible risk factors causing anomalies in the fetus. Gastroschisis is a congenital anomaly of the abdominal wall that is more common in pregnant adolescents. This damage is generally believed to be the result of early embryonic vascular damage. The relationship between vasoactive effects (as an indicator of blood damage) and the risk of gastroschisis during pregnancy is evaluated. Pregnancy in adolescents is considered a recognized risk factor; in a study by Goldbaum et al., a higher risk of gastroschisis was found in patients under 20 years of age, with a high incidence in patients under 18 years of age. However, there are other studies that have found similar results, proving that young maternal age is the main risk factor. (Andrés Conde*, 2013). In this regard, the development of the clinical case occurs at the Martin Icaza General Hospital, a second-level hospital in Ecuador, a regional reference, and belonging to the Ministry of Public Health (MSP), in which the case of a patient is presented. 14-year-old pregnant adolescent, with a newborn of 37 weeks of gestation by Capurro with a diagnosis of gastroschisis in the year 2022. After birth, the protruded intestines are covered with wet compresses and evaluated by a specialist to begin the treatment of this congenital defect. The present research encourages the importance of carrying out prenatal check-ups in a timely manner during pregnancy in order to identify possible risk factors that may endanger the mother and fetus and provide timely and appropriate obstetric conduct regarding the malformation that is diagnosed.